2017
DOI: 10.1016/j.ebiom.2016.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mucosal Defense and Reduced Tumor Burden in Mice with the Compromised Negative Regulator IRAK-M

Abstract: Aberrant inflammation is a hallmark of inflammatory bowel disease (IBD) and colorectal cancer. IRAK-M is a critical negative regulator of TLR signaling and overzealous inflammation. Here we utilize data from human studies and Irak-m−/− mice to elucidate the role of IRAK-M in the modulation of gastrointestinal immune system homeostasis. In human patients, IRAK-M expression is up-regulated during IBD and colorectal cancer. Further functional studies in mice revealed that Irak-m−/− animals are protected against c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…Interestingly, in these initial studies, Irak-m −/− mice do not display enhanced morbidity or mortality following infection, despite the increased inflammation [47]. These findings are consistent with a more recent study that showed the Irak-m −/− mice are protected in models of experimental colitis and colitis associated tumorigenesis [56]. Mice lacking IRAK-M were found to have a robust immune response to bacteria translocating from the lumen following chemical induced damage to the intestinal epithelial cell barrier [56].…”
Section: Transcription Inhibitionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, in these initial studies, Irak-m −/− mice do not display enhanced morbidity or mortality following infection, despite the increased inflammation [47]. These findings are consistent with a more recent study that showed the Irak-m −/− mice are protected in models of experimental colitis and colitis associated tumorigenesis [56]. Mice lacking IRAK-M were found to have a robust immune response to bacteria translocating from the lumen following chemical induced damage to the intestinal epithelial cell barrier [56].…”
Section: Transcription Inhibitionsupporting
confidence: 82%
“…Mice lacking IRAK-M were found to have a robust immune response to bacteria translocating from the lumen following chemical induced damage to the intestinal epithelial cell barrier [56]. The attenuation in pathogenesis was associated with large expansions of gastrointestinal associated lymphoid tissue (GALT), increased neutrophil function, and enhanced T-cell recruitment [56]. Complementary data revealed that the gastrointestinal (GI) tract of the Irak-m −/− mice had a lower total colonic bacterial load compared to wild type counterparts, which could also contribute to attenuation of disease pathogenesis [57].…”
Section: Transcription Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR and WNT activation in tumor cells drive IRAK-M expression, which promotes tumorigenesis by preventing STAT3 proteasomal degradation (25). Another study confirmed the protective role of IRAK-M against AOM/DSS-induced tumorigenesis, although the authors reported resistance to DSS colitis and attenuation of intestinal microbial translocation in Irak-m -/- mice(26). …”
Section: Innate Sensors and Immune Signalingmentioning
confidence: 86%
“…IRAK-M is a negative regulator of TLR/NK-κB signaling and found to be upregulated in IBD and CRC patients (25, 26). Irak-m -/- mice showed enhanced colitis but reduced tumorigenesis following AOM/DSS treatment (25).…”
Section: Innate Sensors and Immune Signalingmentioning
confidence: 99%